The ECB's Money Pillar : An Assessment - Jaeger, Albert (IMF Working Papers; Working Paper, 2003)
This paper discusses the case for a money pillar in the European Central Bank's (ECB) monetary policy strategy. Time-series evidence for industrial countries based on frequency-domain and unobserved-components analysis suggests that money can play a useful role in gauging and constraining long-run risks to price stability. Moreover, the specter of asset price bubbles and some of the area's institutional features, which may impart considerable persistence to area-wide inflation, caution against shifting to conventional inflation targeting. But the time series evidence also seems to point to a relatively loose connection between variations in nominal money growth and inflation in the short to medium run. As a consequence, effective communication of the ECB's monetary policy decisions from the point of view of the present money pillar is likely to remain a challenging task.